2003
DOI: 10.1177/154411130301400207
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Behavior of the Temporomandibular Joint Disc

Abstract: The temporomandibular joint (TMJ) disc consists mainly of collagen fibers and proteoglycans constrained in the interstices of the collagen fiber mesh. This construction results in a viscoelastic response of the disc to loading and enables the disc to play an important role as a stress absorber during function. The viscoelastic properties depend on the direction (tension, compression, and shear) and the type of the applied loading (static and dynamic). The compressive elastic modulus of the disc is smaller than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
193
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(201 citation statements)
references
References 89 publications
(177 reference statements)
3
193
2
Order By: Relevance
“…TMJ tissues are mostly subjected to dynamic loading during chewing or talking, although static and quasi-static loading arising from clenching or grinding may also be prevalent depending on personal habits (Tanaka and van Eijden 2003;Kuroda et al 2009). Unlike hyaline cartilage in other joints, the TMJ disc and condylar cartilage are fibrocartilaginous tissues with a unique composition and structure (Tanaka and van Eijden 2003;Kuroda et al 2009). A dense fibrous zone composed of anteroposteriorly aligned large type I collagen bundles covers the top of the condylar cartilage, resulting in a surface roughness that is an order of magnitude higher than that of hyaline cartilage in the knee joint (Chan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMJ tissues are mostly subjected to dynamic loading during chewing or talking, although static and quasi-static loading arising from clenching or grinding may also be prevalent depending on personal habits (Tanaka and van Eijden 2003;Kuroda et al 2009). Unlike hyaline cartilage in other joints, the TMJ disc and condylar cartilage are fibrocartilaginous tissues with a unique composition and structure (Tanaka and van Eijden 2003;Kuroda et al 2009). A dense fibrous zone composed of anteroposteriorly aligned large type I collagen bundles covers the top of the condylar cartilage, resulting in a surface roughness that is an order of magnitude higher than that of hyaline cartilage in the knee joint (Chan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During physiological function, the soft tissues in the TMJ are subjected to tensile, compressive, and shear loads due to a combination of translational and rotational movements (Tanaka and van Eijden 2003;Kuroda et al 2009). TMJ tissues are mostly subjected to dynamic loading during chewing or talking, although static and quasi-static loading arising from clenching or grinding may also be prevalent depending on personal habits (Tanaka and van Eijden 2003;Kuroda et al 2009). Unlike hyaline cartilage in other joints, the TMJ disc and condylar cartilage are fibrocartilaginous tissues with a unique composition and structure (Tanaka and van Eijden 2003;Kuroda et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…20 It has been reported that the content of glycosaminoglycan, a polysaccharide attached to a core protein in proteoglycan, in the articular disk of the TMJ in patients with anterior disk displacement and those with chronic closed lock is considerably lower than that observed in normal disk tissue. 21,22 Therefore, the composition of the articular disk is thought to change under the above conditions.…”
mentioning
confidence: 99%
“…Bioengineers worldwide have made major strides in modeling the TMJ, with major contributions from groups in Japan, 78,[89][90][91][92][93][94][95][96][97][98] the Netherlands, [14][15][16][53][54][55][56][57][58][59][60]102 Spain, [73][74][75][76] and Switzerland. 34,35,61 An excellent review of TMJ biomechanical models was provided by Koolstra 53 in 2003, and significant progress has been made since then by the aforementioned groups and others.…”
Section: Directives From the Clinical Communitymentioning
confidence: 99%